The Influence Of Accountability And Professionalism of Auditors Partially And Simultaneously on The Quality Of Audits at The Public Accounting Firm In Makassar City And Gowa Regency - Sudirman abdi; Rachmat Rachmat; Haliah Haliah; andi Kusumawati (Economy Deposit Journal (E-DJ), 2022)
The study aims to find out how the influence of accountability and professionalism of auditors partially and simultaneously on the quality of audits at the Public Accounting Firm in Makassar City and Gowa Regency. This research using a descriptive quantitave approach was obtained through the distribution of research questionnaires to respondents, namely auditors who work at the Public Accounting Firm in Makassar City and Gowa Regency. And then the method analysis using multiple regression analysis that’s contain data quality test (validity and reliability), the classics assumption test, coefficient determinant test, t test, and F test. The results showed that the accountability variable had meaning that accountability partially had a positive and significant effect on audit quality at the Public Accounting Firm in the City in the City Makassar and Gowa Regency. Furthermore, the auditor's professionalism variable had which means that the professionalism of the auditor partially has a positive and significant effect on the quality of the audit at the Public Accounting Firm in the City in the City Makassar and Gowa Regency. simultaneously that the accountability and professionalism of the auditor has a positive and significant effect on the quality of the audit at the Public Accounting Firm in the City in the City Makassar and Gowa Regency